2017
DOI: 10.1002/alr.22033
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of nasal irrigation with 200 μg/mL amphotericin B after functional endoscopic sinus surgery: a randomized, placebo‐controlled, double‐blind study

Abstract: Background Previous studies have shown controversial results of topical amphotericin B (AMB) nasal irrigation for chronic rhinosinusitis (CRS). The purpose of this study was to evaluate the efficacy of 200 μg/mL AMB nasal irrigation as an adjuvant therapy after functional endoscopic sinus surgery (FESS). Methods Patients with CRS who had received FESS for treatment were recruited and assigned to 1 of 2 groups at random at 1 month postsurgery. In the AMB group patients received nasal irrigation with 200 μg/mL o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Liang et al definitively excluded CRSwNP cases 1164 and 1 study did not provide details about whether participants had NPs 1163 . Five studies cited NPs as an inclusion criterion; 1165–1169 the remaining 4 studies reported polyps in 20%, 1170 35.6%, 1171 43.8% 1162 , and 81.9% 1172 of participants. Four studies excluded patients with AFRS 1165–1167,1172 and 1 study reported on double density signs and positive fungal cultures being present in 29% and 30% of cases, respectively, but did not definitively diagnose AFRS 1168 .…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al definitively excluded CRSwNP cases 1164 and 1 study did not provide details about whether participants had NPs 1163 . Five studies cited NPs as an inclusion criterion; 1165–1169 the remaining 4 studies reported polyps in 20%, 1170 35.6%, 1171 43.8% 1162 , and 81.9% 1172 of participants. Four studies excluded patients with AFRS 1165–1167,1172 and 1 study reported on double density signs and positive fungal cultures being present in 29% and 30% of cases, respectively, but did not definitively diagnose AFRS 1168 .…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…From the 11 studies that investigated the use of topical antifungal agents, amphotericin B was used in 10 studies and fluconazole in only 1 study. The Cochrane review of 2018 summarized the evidence for topical antifungals 618 and there were 3 additional RCTs published after the review that have been included here 1168,1170,1171 . The delivery methods varied among the studies with nasal irrigations being most popular, 1164,1168,1170–1172 followed by syringe delivery; 1163,1165,1166 Weschta et al and Gerlinger et al used a spray delivery method 1167,1169 and Hashemian et al formulated the fluconazole as nasal drops 1162…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…However, a study on the safety of a novel formulation of nanodisc (ND) containing super aggregated AMB (ND-AMB) for sinonasal delivery has recently demonstrated apically administered 75 μg/mL ND-AMB or AMB solution for 15 minutes to insignificantly alter the CBF of human nasal epithelial cells grown as air-liquid interface cultures 44. More recently, Jiang and colleagues45 evaluated the efficacy of AMB nasal irrigation as adjuvant therapy after functional endoscopic sinus surgery (ESS) on chronic rhinosinusitis patients, and demonstrated that nasal irrigation with 200 μg/mL AMB for 2 months did not significantly alter saccharine transit time, compared to pre-irrigation. The influence of different antimicrobials and antivirals on human nasal mucociliary clearance and CBF is summarized in Table 4.…”
Section: Effects Of Intranasal Antimicrobials and Antiviralsmentioning
confidence: 99%
“…Saline irrigation is mostly acceptable. Antimicrobial agents as antibiotics or antifungal agents had been added to the irrigation fluid [ 14 16 ]. Some researchers had also used additives as manuka honey, xylitol, or surfactant for improvement of the effect of nasal irrigation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%